Psychosocial Influence of Malocclusion Among Nepalese Patients Seeking Orthodontic Treatment: A Hospital Based Cross-Sectional Study - Shrestha, Raju; Halwai, Hemant Kumar; Yadav, Sumit Kumar; Gupta, Sandeep Kumar (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Traditionally, orthodontic treatment focuses on normative criteria, though psychosocial dimension has equal importance. The aim of the study was to evaluate the psychosocial impact of malocclusion among patient seeking orthodontic treatment using psychosocial impact of dental aesthetics questionnaire (PIDAQ). MATERIAL AND METHODS A cross-sectional study was conducted in Department of Orthodontics and Dentofacial Orthopedics, UCMS during the period of July 2021 to Dec 2021. The study was approved by Institutional Review Committee of UCMS (IRC/081/21). Sixty patients seeking orthodontic treatment of age group 18-30 years answered questions concerning self perceived psychosocial impacts of malocclusion using Nepali version of PIDAQ, desire of orthodontic treatment based on scale ranging from 0 to 4. Clinical examination was performed to assess the severity of malocclusion based on the basis of Dental Health Component of Index of Orthodontic treatment need (IOTN-DHC). RESULTS Results showed no signiﬁcant differences in total PIDAQ scores and its subscale (p>0.05) among genders. There was signiﬁ- cant difference in total PIDAQ scores and its subscale (p<0.05) among patients with different desire of orthodontic treatment. Patient with very strong desire have the highest scores of total PIDAQ (42.27±11.40).Signiﬁcant difference in total PIDAQ score and its subscale (p<0.05) was seen among patients with difference grades of IOTN-DHC. CONCLUSION Equal self-perceived impacts of malocclusion were seen in both male and female. There was greater desire of Orthodontic treatment in patients with increased self-perceived psychosocial impact of malocclusion. Signiﬁcant increase in PIDAQ score was also seen with increasing severity of malocclusion.